Pemerintah dalam Kacamata Gamers (Peran Fasilitas dan Pembinaan) Atlet E-Sports di Kota Palembang - Chusnul Hidayat, Rajas; Kencana, Novia; Kariem, Muhammad Qur'anul (Universitas Indo Global Mandiri, 2023)
This research discusses governance from the perspective of gamers (the role of facilities and development) of e-sports athletes in the city of Palembang. The aim of this research is to find out the government's role in developing e-sports athletes in Palembang City andalso to provide information to professional players regarding the development of e-sports athletes in Palembang City. The method used in this research is a qualitative method using Jim Ife's role theory which consists of 4 aspects, namely the role of facilitator, the role of education, the role of representational and the role of technical ability. The results of this research include first, the facilities provided to Palembang esports to date have not been adequate or optimal; secondly, currently the esports coaches or coaches themselves have not been provided by the relevant agencies and there has also been no socialization regarding the coaching of esports athletes themselves; third, Dispora has not carried out and organized events or competitions because there is no readiness to organize the event itself; And fourth, until now the Dispora has not carried out its own selection process but rather the selection process is carried out directly by the respective communities.